Study of SO2 Pollution in the Middle East Using MERRA‐2, CAMS Data Assimilation Products, and High‐Resolution WRF‐Chem Simulations. Issue 6 (21st March 2020) - Ukhov, A.; Mostamandi, S.; Krotkov, N.; Flemming, J.; da Silva, A.; Li, C.; Fioletov, V.; McLinden, C.; Anisimov, A.; Alshehri, Y. M.; Stenchikov, G.
Abstract: Oil recovery, power generation, water desalination, gas flaring, and traffic are the main contributors to SO 2 emissions in the Middle East (ME). Satellite observations suggest that the traditional emission inventories do not account for multiple SO 2 emission sources in the ME. This study aims to evaluate the most frequently used SO 2 emission data sets over the ME by comparing high‐resolution regional model simulations and meteorology/chemistry assimilation products, MERRA‐2 and CAMS, with satellite and available ground‐based air‐quality observations. Here, we employ the WRF‐Chem‐3.7.1 regional meteorology‐chemistry model and conduct simulations for the period 2015–2016 with 10 km grid spacing using HTAP‐2.2 emission data sets and the new OMI‐HTAP data, which is based on the combination of the near‐surface SO 2 emissions taken from the HTAP‐2.2 inventory with strong (>30 kt/year) SO 2 point sources obtained from the satellite Ozone Monitoring Instrument (OMI) observations. We find that conventional emission inventories (EDGAR‐4.2, MACCity, and HTAP‐2.2) have uncertainties in the location and magnitude of SO 2 sources in the ME and significantly underestimate SO 2 emissions in the Arabian Gulf. The WRF‐Chem, run in conjunction with the new OMI‐HTAP emissions, improves comparisons between the satellite and ground‐based SO 2 observations. Our simulations show that SO 2 surface concentrations in Jeddah and Riyadh frequently exceed European air‐quality limits. The ME generates about 10% of global anthropogenic SO 2 emissions, on par with India. Therefore, the development of effective emission controls and improvement of air‐quality monitoring in the ME are urgently needed. Key Points: Anthropogenic emissions and their vertical distribution are the critical factors for simulating air pollution Fine‐resolution WRF‐Chem simulations with the most accurate SO 2 "top‐down" emissions agree well with observations In Riyadh and Jeddah, the European SO 2 air‐quality limit (125  μ g/m 3 ) is exceeded in about 75 days/year